The evaluation of a surgery and the short-term benefits of a new active bone conduction hearing implant - the Osia® - Gawęcki,Wojciech (2022)
Abstract Introduction Modern medicine offers a wide spectrum of different hearing devices, and bone conduction implants can be found among them. Objective The presentation of the outcomes of the implantation of a new active bone conduction hearing implant - the Osia®, and its comparison with the well-known passive transcutaneous system - the Baha® Attract. Methods Eight adult patients with bilateral mixed hearing loss were randomly divided into two groups. Group 1 was implanted with the Osia®, and group 2 was implanted with the Baha® Attract. The details of the surgery were analyzed, along with the functional and audiological results. Results In all the cases, the surgery was successful, and the healing uneventful. In both groups, it was observed that pure tone audiometry and speech audiometry in free field improved significantly after the implantation (mean gain in pure tone audiometry for the Osia group 42.8 dB SPL and for the Baha group 38.8 dB SPL). In the Osia group, the results after the surgery were much better than with the Baha® 5 Power processor on the Softband. The patients implanted with the Osia® evaluated the quality of their hearing as being superior to those implanted with the Baha® Attract. There was an evident improvement in the abbreviated profile of hearing aid benefit questionnaire and in the speech, spatial and qualities of hearing scale for both systems. In the abbreviated profile of hearing aid benefit, changes were more evident in the Osia group (in global score 49% vs. 37.2%). Conclusion Implantation of the Osia® is an effective treatment option for the patients with bilateral mixed hearing loss. The surgery is safe but more complex and time-consuming than the Baha® Attract implantation. The preliminary audiological results as well as the overall quality of life indicate that the Osia® is a better solution than the Baha® Attract. However, future studies should be carried out to make further observations in a larger group of patients, and with longer follow-up.